The functional impact of G protein-coupled receptor 142 (Gpr142) on pancreatic β-cell in rodent - Al-Amily, Israa Mohammad (Pflugers Arch, 2019)
We have recently shown that the G protein-coupled receptor 142 (GPR142) is expressed in both rodent and human pancreatic β-cells. Herein, we investigated the cellular distribution of GPR142 within islets and the effects of selective agonists of GPR142 on glucose-stimulated insulin secretion (GSIS) in the mouse islets and INS-1832/13 cells. Double-immunostaining revealed that GPR142 immunoreactivity in islets mainly occurs in insulin-positive cells. Potentiation of GSIS by GPR142 activation was accompanied by increased cAMP content in INS-1832/13 cells. PKA/Epac inhibition markedly suppressed the effect of GPR142 activation on insulin release. Gpr142 knockdown (Gpr142-KD) in islets was accompanied by elevated release of MCP-1, IFNγ, and TNFα during culture period and abolished the modulatory effect of GPR142 activation on the GSIS. Gpr142-KD had no effect on Ffar1, Ffar2, or Ffar3 mRNA while reducing Gpr56 and increasing Tlr5 and Tlr7 mRNA expression. Gpr142-KD was associated with an increased expression of Chrebp, Txnip, RhoA, and mitochondrial Vdac1 concomitant with a reduced Pdx1, Pax6, and mitochondrial Vdac2 mRNA levels. Long-term exposure of INS-1832/13 cells to hyperglycemia reduced Gpr142 and Vdac2 while increased Chrebp, Txnip, and Vdac1 mRNA expression. GPR142 agonists or Bt(2)-cAMP counteracted this effect. Glucotoxicity-induced decrease of cell viability in Gpr142-KD INS-1 cells was not affected by GPR142-agonists while Bt(2)-cAMP prevented it. The results show the importance of Gpr142 in the maintenance of pancreatic β-cell function in rodents and that GPR142 agonists potentiate GSIS by an action, which most likely is due to increased cellular generation of second messenger molecule cAMP. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00424-019-02262-7) contains supplementary material, which is available to authorized users.